Beyond degrees :finding success in higher education - edited by Ira Pande; Pande, Ira.; India International Centre (New Delhi : HarperCollins Publishers India, a joint venture with India Today Group : India International Centre, 2008)
Contributed articles collated under the invitation of the India International Centre on the life and ethos of Indian universities and colleges.
Includes bibliographical references.
Keywords: Education, Higher -- Aims and objectives -- India